Impact of phosphorus and sulphur fertilization on yield and physico-chemical properties of soil in soybean [Glycine max (L.) Merrill] - Manoj,; Manoj Kumar Sharma,; Rajendra Kumar Yadav,; Harphool Meena,; Vinod Kumar Yadav,; Shankar Lal Yadav,; Bahnu Pratap Ghasil, (Annals of Agricultural Research, 2023)
An experiment was conducted on soybean during kharif season of 2021 at Instructional Farm, College of Agriculture, Ummedganj, Kota (Rajasthan). The treatments comprised four levels of phosphorus viz., 0, 20, 40 and 60 kg ha-1 and three levels of sulphur viz., 15, 30 and 45 kg ha-1, thereby making twelve treatment combinations laid out in factorial randomized block design with three replications. The maximum seed yield (1942 kg ha-1)of soybean were recorded with the application of 60 kg P2 O5 ha-1 over application of 20 kg phosphorus ha-1 and control. However, it was found at par with the application of 40 kg P2 O5 ha-1. Significantly higher available nitrogen, phosphorus, potassium and sulphur (292.1,33.8, 413.1 and 22.0 kg ha-1) was recorded with application of 60 kg phosphorus ha-1 over application of 20 kg phosphorus ha-1 and control, but it was found at par with application of 40 kg phosphorus ha-1 in soil after crop harvest. Application of 45 kg sulphur ha-1 produced the maximum seed yield (1870 kg ha-1) of soybean over application of 15 kg sulphur ha-1 but it was found at par with application of 30 kg sulphur ha-1. The maximum available nitrogen, phosphorus, potassium and sulphur (286, 31.5, 411.0 and 20.9 kg ha-1) in soil was recorded with application of 45 kg sulphur ha-1 which was closely followed by 30 kg sulphur ha-1. However, it was found significantly superior over application of 15 kg sulphur ha-1 in soil after crop harvest.